SISTEM INFORMASI PENDAFTARAN SISWA BARU PADA SMKN 2 SUMBAWA BESAR BERBASIS WEB - Eri Sasmita Susanto; Harfina Aprianti; Mila Sejahtera (Jurnal Informatika Teknologi dan Sains, 2020)
Sumbawa Besar 2 Vocational High School is a school where the author conducts research. At this time, the new student registration system, in recording new prospective students still uses books or is conventional, so registration officers experience many problems. The solution to the problem that is happening at Sumbawa Besar 2 Vocational High School is the application of information technology, namely building an information system that can be useful to facilitate the committee and registrants in the New Student Registration process. This system was developed using the Personal Home Page (PHP) and MySql programming languages as a database. The method used in building this system is using the Waterfall method. With the existence of this webbased information system can increase information. Making the registration of new student registration data becomes more structured so that it makes it easier to select new prospective students